PELAKSANAAN SERTIFIKASI HALAL SUPPLIER IKM DI PASAR KUE KECAMATAN PLERED KABUPATEN CIREBON JAWA BARAT - Akhmad Khalimy (Universitas Trunojoyo Madura, 2018)
AbstractSharia tourism is not only related to religious values such as places of pilgrimage and religion but more towards lifestyle. Sharia tourism includes the availability of supporting facilities, such as restaurants and hotels that provide halal food and prayer rooms. Tourist products and services, as well as tourist destinations in Islamic tourism, are the same as tourism in general as long as they are not in conflict with Islamic values and ethics.Thus, halal tourism is supported by a series of interrelated components: travel, hotel, money market, lifestyle; medicines, cosmetics, and food. Food and cakes are one component that will not be overlooked in halal tourism destinations, even it can be said that there is no tourism without food. There is no halal tourism without halal food.Research on the implementation of halal certification by suppliers of Small and Medium Industries (SMI) in Cirebon Plered Cake Market is a qualitative research that reveals the facts about how the suppliers of SMI around Plered Cirebon whose products are consumed outside the district, between provinces and across islands addressing halal certification. This study also presents the factors of the low interest and intention of the suppliers to process halal certificates on their products and the factors that encourage them to be very enthusiastic to certify the cake or food products.Need breakthroughs and coordination from related parties; Government agencies, institutions, traders, so that the implementation of halal certification can run well so that it can support tourism in each region in Indonesia. Keyword: Syaria Tourism, Halal Sertification, Small Medium Industry AbstractWisata syariah tidak hanya melulu terkait dengan nilai-nilai agama seperti tempat ziarah dan religi, tetapi lebih mengarah pada lifestyle.Wisata syariah mencakup ketersediaan fasilitas pendukung, seperti restoran dan hotel yang menyediakan makanan halal dan tempat shalat. Produk dan jasa wisata, serta tujuan wisata dalam pariwisata syariah sama seperti wisata pada umumnya selama tidak bertentangan dengan nilai-nilai dan etika syariah.Dengan demikian pariwisata halal ditunjang oleh rangkaian komponen yang saling terkait: travel, hotel, pasar uang, gaya hidup; obat-obatan, kosmetik dan makananan. Makananan maupun kue menjadi salah satu komponen yang tidak akan terlewatkan dalam destinasi pariwisata halal, bahkan dapat dikatakan tidak ada pariwisata tanpa makan. Tidak ada pariwisata halal tanpa makanan halal.Penelitian tentang pelaksanaan sertifikasi halal oleh supplier IKM di Pasar Kue Plered Cirebon, adalah penelitian kualitatif yang membeberkan fakta tentang bagaimana para supplier IKM di sekitar Plered Cirebon yang produknya dikonsumsi diluar kabupaten, antar propinsi dan lintas pulau menyikapi sertifikasi halal. Penelitian ini juga menyajikan factor-faktor rendahnya minat dan niat para supplier untuk memproses sertifikat halal pada produknya dan faktor-faktor yang mendorong mereka sangat antusias untuk mensertifikasi produk kue atau makananya.Perlu terobosan dan koordinasi dari para pihak terkait; Lembaga pemerintah, institusi, para pedagang, agar pelaksanaan sertifikasi halal dapat berjalan dengan baik, menarik sehingga dapat mendukung parawisata di masing-masing daerah di Indonesia. Keyword: Wisata Syariah, Sertifikat Halal, Industry Kecil Menengah